Kepatuhan Syariah dalam Penerbitan Sukuk: Pendekatan Kualitatif Berbasis Fatwa DSN-MUI dan Peraturan OJK di Indonesia - Ardiansah, Muhamad Resa; Hidayah, Nur; Muhajirin, Muhajirin (Community Engagement and Emergence Journal (CEEJ), 2026)
Objective: This study aims to describe the elements of sharia compliance contained in sukuk, based on the fatwas of the National Sharia Council (DSN-MUI) and several regulations issued by the Financial Services Authority (OJK) in Indonesia. Design/Methodology/Approach: This study uses a qualitative approach with documentary and secondary data, including fatwas and regulations required to explore the sharia compliance of sukuk. This study highlights and identifies the elements of sharia compliance using a hierarchy map. Findings: Sukuk in Indonesia fulfills sharia compliance through: (1) absolute prohibition of riba, gharar, maysir, tadlis, dharar, risywah, zhulm, and haram activities; (2) halal underlying assets (tangible assets, asset benefits, services, certain projects, or certain investment activities) with a minimum of 51 percent tangible assets for traded sukuk; (3) transparent returns in the form of profit sharing, margins, or ujrah in accordance with sharia contracts (mudharabah, musyarakah, ijarah, wakalah, murabahah, salam, istishna'); (4) implementation of maqasid sharia through the principle of "dar' al-mafasid muqaddam 'ala jalb al-masalih" and support for sustainable development (sustainability sukuk). All fatwas and POJK consistently emphasize that sukuk must represent ownership of real assets, not merely interest-bearing debt. Practical Implications: Existing regulations have established a strong sharia compliance framework for sovereign sukuk (SBSN) and corporate sukuk, including sustainable sukuk (green/sustainability sukuk). However, ongoing supervision by the Sharia Supervisory Board and the Sharia Expert Team, as well as transparent reporting on the use of funds, remain essential to maintaining sharia integrity throughout the sukuk lifecycle. Originality/Value: This study provides a hierarchical mapping of the elements of sharia compliance in sukuk in Indonesia by integrating relevant DSN-MUI fatwas and the development of OJK regulations, serving as a reference for further research and practice in Islamic finance.